The Role of Madrasa Heads in Improving the Quality of Islamic Religious Education - Rusdi Rusdi; Syaflin Halim; Rosniati Hakim (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2022)
This study aims to reveal the madrasa head's role in improving the quality of Islamic religious education in Madrasah Ibtidaiyah. This goal is based on the existing problem that the madrasa head's duties are numerous. Therefore, his role in improving the quality of Islamic religious education needs to be the object of study. The research was conducted at Madrasah Ibtidaiyah Negeri (MIN) 3 Padang City. The research method is qualitative, with data collected through observation, interviews, and documentation studies. The results of the research are as follows first, the head of the madrasa plays a role in improving the quality of Islamic religious education in his position as an educator, such as realizing a conducive madrasa environment, directing madrasa residents to implement Islamic values ​​in the madrasa environment, and involving Islamic religious educators in training activities or workshops so that The ability of educators is upgraded and in accordance with the times. Second, the supporting factors experienced by madrasa heads in improving the quality of Islamic religious education are the active cooperation and participation of all elements in the madrasa environment. The inhibiting factor for madrasa heads to improve the quality of Islamic religious education is that the managed DIPA funds are not balanced with the needs of madrasas.